2022
DOI: 10.1111/pcmr.13069
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study to sequentially determine the dermoscopic features of vitiligo and its association with disease activity in patients on medical treatment

Abstract: Vitiligo is a common acquired disorder of depigmentation caused due to loss of melanocytes. The dark complexion of ethnic skin combined with social stigma and lack of knowledge about the disease in the general population causes a lot of psychological distress to affected patients (Parsad et al., 2003). Treatment in vitiligo is often guided by the disease activity as well as its extent. Though various scoring systems like vitiligo disease activity index (VIDA), vitiligo activity severity index (VASI) and vitili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Prior studies have linked dermoscopic signs like perifollicular depigmentation and micro-Koebner phenomenon to disease activity. 14,15 However, in the present study our focus was on visible clinical signs of disease activity because a standardised scoring instrument is already available and validated (VSAS). Further elaboration of the dermoscopic signs and their connection to disease activity would be an interesting topic.…”
Section: Discussion/con Clus Ionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have linked dermoscopic signs like perifollicular depigmentation and micro-Koebner phenomenon to disease activity. 14,15 However, in the present study our focus was on visible clinical signs of disease activity because a standardised scoring instrument is already available and validated (VSAS). Further elaboration of the dermoscopic signs and their connection to disease activity would be an interesting topic.…”
Section: Discussion/con Clus Ionmentioning
confidence: 99%
“…Further research focusing on the impact of treatment on the disease activity sign would be valuable. Prior studies have linked dermoscopic signs like perifollicular depigmentation and micro‐Koebner phenomenon to disease activity 14,15 . However, in the present study our focus was on visible clinical signs of disease activity because a standardised scoring instrument is already available and validated (VSAS).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Pigment network changes, such as altered, reduced, and reversed pigment network, could be a marker of disease activity, as they are observed more in active disease than in stable or repigmenting vitiligo. 34,36,37 Reticulate pigment network, on the other hand, has been associated with stable vitiligo. 35 Conflicting results have been reported on perifollicular pigmentation and perifollicular depigmentation.…”
Section: Part 2: Dermoscopic Markersmentioning
confidence: 99%
“…Perifollicular pigmentation is linked to active vitiligo in a case series and retrospective analysis by the same author, while an observational study observed perifollicular repigmentation as a marker of lesional stability or repigmentation. 34,36,37 Perifollicular depigmentation has been associated with stable disease; however, another study linked this feature to active disease. 34,36,37 Other features such as starbust appearance, comet tail appearance, tiny pearly white globules, and tapioca sago were exclusively observed in active disease.…”
Section: Part 2: Dermoscopic Markersmentioning
confidence: 99%
See 1 more Smart Citation